THE ENFORCEMENT PROCEEDING UNDER THE BULGARIAN ADMINISTRATIVE PROCEDURE CODE (World Science, 2021)
This paper considers the issues related to the provisional enforcement of administrative acts and the legal remedies against the execution of an administrative act before its entry into force in case of contestation before a higher administrative body or the court. The means of protection of the parties concerned against the provisional enforcement of administrative acts are the subject of special proceedings defined as enforcement proceedings, as they guarantee the ultimate aim of protecting the respective appellant, which is sought by challenging the administrative act, namely not to have the legal consequences of an illegal administrative act realized. The enforcement proceedings under the Administrative Procedure Code provide protection through the suspension of provisional enforcement until the final settlement of the issue of the legality of the administrative act. There detailed consideration of the preconditions of the proceedings, including the controversial issues related to their application in the administration of justice.